ATRT-26. META-ANALYSIS OF TREATMENT MODALITIES IN METASTATIC ATYPICAL TERATOID/RHABDOID TUMORS IN CHILDREN. (4th December 2020) - Underiner, Reena M; Eltobgy, Mostafa; Stanek, Joseph R; Finlay, Jonathan L; AbdelBaki, Mohamed S
Abstract: BACKGROUND: Metastatic atypical teratoid/rhabdoid tumors (AT/RT) are aggressive central nervous system tumors that present during infancy and are associated with dismal outcomes. Patients receive multimodal treatment including surgical resection, systemic chemotherapy and one or more of intrathecal chemotherapy (IT), marrow-ablative chemotherapy with autologous hematopoietic cell rescue (AuHCR) and radiation therapy (XRT). While data regarding treatment modalities for AT/RT patients exist, no comprehensive data have been published regarding the metastatic patient population. METHODS: We performed a meta-analysis of 1, 578 articles published through September 2018, including 44 studies with a total of 123 subjects. Additionally, seven patients were incorporated through chart review of patients treated at Nationwide Children's Hospital. RESULTS: Analysis of 130 patients revealed a 3-year overall survival (OS) of 25%. Age at diagnosis had a significant impact on survival (p=0.0355); 3-year OS for infants < 18 months was 21%; 18–36 months was 26%; and > 36 months was 36%. Location of the primary tumor, metastatic stage and extent of surgical resection did not have significant impact on OS. On univariate analysis, XRT (p<0.0001), IT (p=0.01) and AuHCR (p<0.0001) were found to significantly improve survival. The most substantial effect was noted in patients who received AuHCR (3-year OS of 60% versus 9% in those who did not). On multivariable analysis XRT (p=0.0006), IT (p=0.0124) and AuHCR (p<0.0001) were independently associated with reduced risk of death.